PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBASIS MASALAH TERHADAP HASIL BELAJAR IPS PESERTA DIDIK KELAS VIII SMP NEGERI 1 TRIMURJO - Lutfi Annisa; Wakijo Wakijo (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
Make A Match is a group learning model that invites students to understand a concept or topic through paired card games that can make students more active in following the learning process in the classroom so that students can improve their learning outcomes. The problem in the research conducted by researchers is